Implication of Monitoring and Evaluation of School Quality - Afriani Nasution; Faisal Rahman Dongoran; Ali Sadikin; Tumpak Banurea; Tiarma Sidabutar (LP2M STIT Palapa Nusantara, 2023)
The quality of education is a benchmark for parents to choose their child's school, so it requires regular monitoring and evaluation. This study aims to analyze the implications of monitoring and evaluation of school quality. The background of this research took place at One Roof Junior High School 4, STU Jehe, Pakpak Bharat Regency. The approach used in this research is a qualitative approach and the type of research is field research. Collecting data in this study using interviews, observation and documentation. Data analysis used is data reduction technique, data presentation, conclusion and verification. The results of this study concluded that supervision activities using individual and group techniques as a result of monitoring and evaluation have succeeded in improving the quality of education. Then supervision activities include monitoring, coaching, guidance and training, as well as assessments which greatly impact the implications of monitoring and evaluating school quality improvement. Supporting factors in the form of cooperation and mutual support are one of the keys to successful implementation.